Impacts of Climate Change in Portugal: Common Perception of Causes AND Consequences in Forest Development - Nunes, Leonel (2020)
Presently the world faces what most likely will be the greatest challenge humanity has ever faced. Climate change is a phenomenon, or rather a set of phenomena, that directly influences the daily lives of human populations all over the planet. However, this influence normally negative also affects ecosystems, with emphasis on agroforestry systems, of which human populations are directly dependent on food and in a large number of primary raw materials. It is with this premise as a starting point that this work makes an analysis on the current state of climate change in Portugal, since, being a country of Mediterranean climate influence, it should be one of the territories where changes will be felt with more intensity and severity. In this work, the current position on energy production in Portugal regarding Green House Gases (GHGs) emissions and the evolution prospects for the near future, namely in the perspective of the impacts caused on forest resources, are discussed.